The Chemical Compositions, and Antibacterial and Antioxidant Activities of Four Types of Citrus Essential Oils - Lin, Xiaocai; Cao, Shan; Sun, Jingyu; Lu, Dongliang; Zhong, Balian; Chun, Jiong (Molecules (Basel, Switzerland), 2021)
Nanfeng mandarins (Citrus reticulata Blanco cv. Kinokuni), Xunwu mandarins (Citrus reticulata Blanco), Yangshuo kumquats (Citrus japonica Thunb) and physiologically dropped navel oranges (Citrus sinensis Osbeck cv. Newhall) were used as materials to extract peel essential oils (EOs) via hydrodistillation. The chemical composition, and antibacterial and antioxidant activities of the EOs were investigated. GC-MS analysis showed that monoterpene hydrocarbons were the major components and limonene was the predominate compound for all citrus EOs. The antibacterial testing of EOs against five different bacteria (Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Salmonella typhimurium) was carried out using the filter paper method and the broth microdilution method. Kumquat EO had the best inhibitory effect on B. subtilis, E. coli and S. typhimurium with MIC (minimum inhibitory concentration) values of 1.56, 1.56 and 6.25 µL/mL, respectively. All citrus EOs showed the antioxidant activity of scavenging DPPH and ABTS free radicals in a dose-dependent manner. Nanfeng mandarin EO presented the best antioxidant activity, with IC50 values of 15.20 mg/mL for the DPPH assay and 0.80 mg/mL for the ABTS assay. The results also showed that the antibacterial activities of EOs might not be related to their antioxidant activities.